Analisis Strategi Pemasaran dalam Upaya Meningkatkan Pendapatan dan Produktivitas Petani dalam Perspektif Ekonomi Regional (Studi Pada Petani Jagung di Desa Planggiran Kecamatan Tanjungbumi Kabupaten Bangkalan) - Hotimah Hotimah; Aldilla Septiana; Aulia Dawam (Universitas Batanghari, 2022)
In Indonesia, especially in Madura, agriculture is something that is very important for people's lives. Agriculture plays an important role in supporting the availability of food sources for the community, in Indonesia, especially in Madura, precisely in Planggiran village, Tanjungbumi district, Bangkalan district itself has various agricultural products, which include corn, rice, soybeans, chilies, green beans, peanuts. , long beans, and cassava and so on. Because Indonesia is a large part of the area that has the potential to be used as agricultural land. With the existence of agriculture not only as a producer of food but also as a provider of jobs for the community itself. Corn is one type of agriculture that is mostly occupied by farmers in the village of Planggiran. Corn is one type of agriculture that is mostly occupied by farmers in the village of Planggiran. However, even though many are farming corn, farmers' income has not been maximized due to a lack of strategy in terms of marketing. Based on the above background, researchers are interested in conducting research on